Konsumsi Daun Kelakai (Stenochlaena pallustris) Pada Produksi ASI - Nina Rahmadiliyani; Dailila Audita (HB PRESS, 2017)
Traditionally, Dayak people in Central Kalimantan consumption Stenochlaena pallustris plants to stimulating milk production for new mothers. This is due to the nutritional value of Stenochlaena pallustris that contains lots of Fe. Fe element is useful in overcoming anemia problem, so consuming Stenochlaena pallustris can increase blood volume that stimulate milk production. This study aims to determine the effect of consumption of leaves Stenochlaena pallustris to the production of breastfeeding of postpartum mothers at the public health center of Gambut. This research use analytic survey design with cross sectional approach. The population of this research is all postpartum in Public Health Center of Gambut counted 75 people with sampling technique that is total sampling. The research instrument used is a checklist.The result of this research was the most of the respondents (66,7%) not consuming the Stenochlaena pallustris and the most of the respondents have production of ASI is sufficient that is 58 respondents (77,3%). Based on correlation analysis there is no influence of leaves consumption of Stenochlaena pallustris to milk production. It is expected that health workers, especially midwives, provide counseling or health education on how to process leaves Stenochlaena pallustris